Cross-cultural adaptation and validation of the Chinese version of the PSS-QoL questionnaire. - Yu Zhou; Linli Zhuang; Xiaoqin He; Li Xu; Qi He; Xuemei Li; Yali Ye (PLoS ONE)
Background The quality of life(QoL) of patients with primary Sjögren's syndrome(PSS) is affected by a variety of symptoms, and it is important to comprehensively assess the factors affecting patients' QoL.The PSS-QoL is a specific tool for the assessment of patients' QoL in the PSS. The purpose of this study was to cross-culturally adapt the PSS-QoL for the Chinese language,to establish a QoL assessment tool for PSS patients in Chinese culture and to test the reliability and validity of the PSS-QoL. Methods Our study period was from January 17, 2024 to June 15, 2024. The study was designed as a two-stage observational study. Double forward and backward translations of the PSS-QoL were performed for cultural adaptation to the Chinese language,and the specific steps included forward and backward translations, coordination, expert correspondence, small-sample surveys, and corrections to form the final draft of the Chinese version of the PSS-QoL. From January 29, 2024 to June 15, 2024,for the evaluation of psychometric properties, 135 patients with PSS completed the Chinese version of the PSS-QoL,Short Form-12(SF-12) and EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI).After 2 to 4 weeks,15 patients with PSS completed the Chinese version of the PSS-QoL for the second time.We used SPSS 26.0 software to statistically analyze the data, including item analysis and reliability and validity tests. Results The Chinese version of the PSS-QoL consists of 25 questions and can be divided into two main categories: physical (discomfort and dryness) and psychosocial. The mean score on the Chinese version of the PSS-QoL was 40.46±15.00. Among the 135 patients with PSS,92.60% were female, the mean (±SD) age was 52.76±12.74 years, and the disease duration was 5 (1.5, 9) years. There was good differentiation between the individual items and the Chinese version of the PSS-QoL,as the decision value of all the items ranged from -3.223 to -12.234 (p < 0.05), the correlation coefficient between the individual items and the whole questionnaire ranged from 0.315 to 0.730 (p < 0.05), the Chinese version of the PSS-QoL had good reliability and validity,as Cronbach's α = 0.886, the Spearman-Brown coefficient was 0.782,the reliability of the individual items was 0.89,and the values of the I-CVI and S-CVI/AVE were all 1, indicating good psychometric properties. The construct validity between the Chinese version of the PSS-QoL and the ESSPRI was excellent (p = 0.506 ~0.687), and that between the PSS-QoL and the SF-12 was good(p = -0.464 ~ -0.673). Conclusion The Chinese version of the PSS-QoL possesses good reliability and validity, and all the indicies meet the metrics and satisfy the psychometrically acceptable range;therefore, it can be used as a reliable instrument for assessing the QoL of patients with PSS in China.